Sensing Characteristics of Nanostructured SnO2 Thin Films as Glucose Sensor. (July 2017) - Haider, Adawiya J.; Jasim Mohammed, Ali; Shaker, Suaad S.; Yahya, Khaled Z.; Haider, Mohammed J.
Abstract: Thermal evaporated Sn thin film was deposited followed by atmospheric oxidation annealing at 550°C for 1 h to fabricate nanostructured SnO2 thin film sensor. The nanostructures were characterized through X-ray diffraction, scanning electron microscopy (SEM) and electrochemical amperometric glucose (C6 H12 O6 ) sensing. The obtained film was strongly c-axis oriented along (100) direction and has other low intensity towards the directions 101, 200 and 211, indicating polycrystalline characteristics. The film exhibited high dense porous nature has been indicated in the SEM images. Furthermore, the glucose sensing properties of the as-prepared SnO2 thin film were investigated for various glucose concentrations (50, 100, 150 and 200) mg/L. The nanostructured SnO2 thin film exhibited a higher response, fast rise time 8s and suitable recovery time 53s upon working at room temperature. Linear relative response with the glucose concentrations for SnO2 thin film biomedical sensor was obtained.